Meningiomas: MRI and Pathological Findings - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
MRIs and histopathological studies of five children, aged 3 months to 16 years, with extra-axial meningiomas are reported from the Arkansas Children's Hospital and University of Arkansas for Medical Sciences, Little Rock, AR.